2022
DOI: 10.1242/jeb.242949
|View full text |Cite
|
Sign up to set email alerts
|

Design of a robotic zebra finch for experimental studies on developmental song learning

Abstract: Birdsong learning has been consolidated as the model system of choice for exploring the biological substrates of vocal learning. In the Zebra Finch (Taeniopygia guttata), only males sing and they develop their song during a sensitive period in early life. Different experimental procedures have been used in the laboratory to train a young finch to learn a song. So far, the best method to get a faithful imitation is to keep a young bird singly with an adult male. Here we present the different characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…The observation that the juveniles exposed to the synchronised RoboFinch stopped singing during presentations shows that these tutees behaved most similar to live tutored birds when exposed to adult tutor song. This is different from an operant use of an animated zebra finch model (Araguas et al, 2022), where tutees that actively approached the animated model were rewarded with song by the experimenter (here the model was thus reacting to the tutees, not vice versa as in live tutoring and our setup). With these reversed contingencies, the operant tutor group in this other robot study learned comparably well as a control live tutored group, when both groups got 1 h/day with the respective models.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The observation that the juveniles exposed to the synchronised RoboFinch stopped singing during presentations shows that these tutees behaved most similar to live tutored birds when exposed to adult tutor song. This is different from an operant use of an animated zebra finch model (Araguas et al, 2022), where tutees that actively approached the animated model were rewarded with song by the experimenter (here the model was thus reacting to the tutees, not vice versa as in live tutoring and our setup). With these reversed contingencies, the operant tutor group in this other robot study learned comparably well as a control live tutored group, when both groups got 1 h/day with the respective models.…”
Section: Discussionmentioning
confidence: 88%
“…With these reversed contingencies, the operant tutor group in this other robot study learned comparably well as a control live tutored group, when both groups got 1 h/day with the respective models. Other studies have used operant tutoring methods but not systematically controlled the presence/absence of visual cues of sound production or looked at contingencies between tutor (song) and tutee behaviour (Araguas et al, 2022; Carouso‐Peck et al, 2020; Carouso‐Peck & Goldstein, 2019; Chen et al, 2016; Derégnaucourt, 2011; Houx & ten Cate, 1999; Tchernichovski et al, 1999). These studies did therefore not address the question as to whether the multimodal nature of the song stimulus is perhaps at the base of improved vocal learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our animations and the use of these animations in conjunction with video game engines (like Unreal Engine) provide a novel way to study social interactions in birds. Recent studies have used a robotic zebra finch for studying social interactions between juvenile birds and a tutor (the robotic bird) (Araguas et al, 2022). While a robot provides physical interactions that animations cannot provide, animations can be built and manipulated more easily.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the visual stimulus of the tutor and possibly social interactions with a tutor are also important for accurate learning. While the mere presence of a visual tutor, in the form of a video, is not sufficient to enhance learning (Varkevisser et al, 2022a), a recent study showed that a robotic zebra finch that vocally interacts with juvenile birds does enhance learning (Araguas et al, 2022). Importantly, the robotic zebra finch provided closed-loop vocal interactions, i.e.…”
Section: Introductionmentioning
confidence: 99%